Life and death in the Neolithic variscite mines at Gavà (Barcelona, Spain). (30th January 2015) - Borrell, Ferran; Bosch, Josep; Majó, Tona
Abstract: Abstract : Mining has commonly been thought of as hard manual labour undertaken by the lower echelon of a hierarchical society, but was this always the case? Recent excavations of the variscite mines at Gavà have revealed burials contemporary with the peak of mining activity that represent a community of miners exploiting the subterranean resources for trade and manufacturing variscite beads with a nuanced symbolism. Skeletal evidence demonstrates the physicality of mining while grave goods reveal a community that worked collectively to mine, manufacture and trade goods, with miners themselves benefiting from the fruits of their labours.